Self-Deception, Beliefs Systems and Self-knowledge’s Errors - Fernández Acevedo, Gustavo (2015)
Richard Holton has criticized the common idea that self-deception is deception by the self, and suggested it is rather deception about the self; self-deception must include necessarily erroneous beliefs about the self. In this article I claim that this condition is not necessary, based on two central traits of self-deception: its temporal character  and  its  bound  to  multiplication.  In  addition,  I  suggest  an  alternative condition in relation to the beliefs system implied in self-deception.